2019
DOI: 10.1002/cpt.1456
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin Dosing Strategy to Achieve Equivalent Exposure Coverage in Children and Adults

Abstract: Ivermectin is a commonly used broad‐spectrum antiparasitic drug, yet doses that produce consistent exposure coverage across age have not been characterized, and no data are available in children weighing < 15 kg. First, a population pharmacokinetic model is developed based on data from 200 children and 11 adults, treated with 100–600 μg/kg ivermectin. Second, model‐based simulations are performed to identify a dosing strategy that achieves equivalent exposure coverage in children and adults. Median (90% confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
(120 reference statements)
3
13
0
Order By: Relevance
“…An open-label pharmacokinetic study of 12 adult volunteers studied multiple covariates including age, sex, height, body weight, body surface area, percentage body fat, gall bladder volume, kidney volume, liver volume, haematocrit, plasma albumin, and MDR1 polymorphism (associated with lower P-glycoprotein pump expression in the intestinal tract) and found only body weight to be significant [20]. The only other study of ivermectin pharmacokinetics in children reported a clearance/kg of 0.35 L/h/kg in children, similar to our results (0.18 L/h/kg) with the difference likely explained by different study populations [13].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…An open-label pharmacokinetic study of 12 adult volunteers studied multiple covariates including age, sex, height, body weight, body surface area, percentage body fat, gall bladder volume, kidney volume, liver volume, haematocrit, plasma albumin, and MDR1 polymorphism (associated with lower P-glycoprotein pump expression in the intestinal tract) and found only body weight to be significant [20]. The only other study of ivermectin pharmacokinetics in children reported a clearance/kg of 0.35 L/h/kg in children, similar to our results (0.18 L/h/kg) with the difference likely explained by different study populations [13].…”
Section: Discussionsupporting
confidence: 87%
“…Our study results are similar to the only other pharmacokinetic study of ivermectin in young children. That study of children living in rural Cote d'Ivoire with Trichuris trichuria infection, showed that doses of 300 μg/kg were required in children aged 2 to 5 years [13]. Previous pharmacokinetic studies in both adults and children have found body weight to be the only significant covariate influencing ivermectin pharmacokinetics, as we found in our study [13,20].…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations